Revisiting metagames and metagaming: theoretical and methodological considerations - Isto Huvila (Informatio)
In the context of information behaviour, metagames and metagaming have been used to refer to information work related second-order activities that go beyond the expected ‘game’ of informational undertakings. This paper continues earlier discussion on informational metagames and metagaming by revisiting the two concepts. It inquires further into how to theorise informational metagames and metagaming in terms of and in relation to what they do to information work, and discuss briefly issues relating to how to study informational metagames and metagaming empirically. It is proposed that metagaming can be conceived as a form of resistance, repair and extension of information work. As an often-invisible activity, the empirical study of metagaming is complicated by the difficulties to identify them, make them visible and to demarcate when an activity qualifies as a metagame. Some of the potential benefit of using metagaming as a lens to inquire into information activities are that it can help to shed light on the constituents and underpinnings of both games and their related metagames and to showcase and explicate the complexity and multi-normativity of information work related second-order activities.